Urothelial Carcinoma: Role of Biomarkers in Diagnosis, Prognosis and Treatment - Ioannis Zachos (Biomedicines)
Urothelial carcinoma (UC), also known as transitional cell carcinoma (TCC), is the second most frequently diagnosed urological tumor worldwide, and typically involves the bladder [...]